2020
DOI: 10.3390/ijms21207505
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Oncolytic Viruses: A Systematic Review

Abstract: Leveraging the immune system to thwart cancer is not a novel strategy and has been explored via cancer vaccines and use of immunomodulators like interferons. However, it was not until the introduction of immune checkpoint inhibitors that we realized the true potential of immunotherapy in combating cancer. Oncolytic viruses are one such immunotherapeutic tool that is currently being explored in cancer therapeutics. We present the most comprehensive systematic review of all oncolytic viruses in Phase 1, 2, and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 128 publications
0
66
0
Order By: Relevance
“…Factors that impair viral proliferation and boost the rate of viral clearance in healthy tissue (IFN type I response genes, tumor suppressor proteins, etc.) are dysfunctional in tumor cells, enabling preferential replication of OVs [ 17 , 18 , 19 ]. Although some viruses exhibit inherent tropism for tumor cells, genetic engineering also helps to precisely tune up the virus life cycle to become the most potent cancer killer [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that impair viral proliferation and boost the rate of viral clearance in healthy tissue (IFN type I response genes, tumor suppressor proteins, etc.) are dysfunctional in tumor cells, enabling preferential replication of OVs [ 17 , 18 , 19 ]. Although some viruses exhibit inherent tropism for tumor cells, genetic engineering also helps to precisely tune up the virus life cycle to become the most potent cancer killer [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…By May 2021, more than 200 clinical trials of diverse combinations of OVs and immunotherapies were found and many others are coming out on the regular basis. Oncolytic virus application is discussed in several immaculate reviews highlighting the results of completed clinical trials [ 18 , 19 ]. In this review, we will discuss combinations of oncolytic viruses and other cancer therapies currently studied in clinical trials with specific emphasis on their efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Various oncolytic viruses have been utilized to employ their tumor-specific killing activities by both direct (e.g., cell lysis due to viral replication and immune-mediated cytotoxicity) and indirect mechanisms (e.g., stimulation of the bystander cell killing, induction of cytotoxicity, etc.) [ 1 , 2 , 3 , 4 , 5 ]. Oncolytic vaccinia virus (VV) is an appealing addition to the current treatment options, demonstrating efficacy and safety in animal models and in early clinical studies [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Big advances have been made in the development of HSV-based oncolytic viruses and the related therapeutic strategies, making HSV a forerunner in the field. Many other oncolytic viruses belonging to different virus families (adenovirus, measles virus, reovirus, vaccinia virus, parvovirus) are already at the clinical trial stage, and accompany oHSVs in their undertaking towards innovative, effective and personalized antitumor strategies [181,182]. The mentioned different virus families have diversified properties, but share similar challenges, notably their intricate relationship with the immune system of the host [162,170,183].…”
Section: Resultsmentioning
confidence: 99%